Effect of plant growth regulators on yield parameters, yield and quality of black pepper (Piper nigram L.) variety Panniyur-1 - Subbiah, A Ramesh Kumar, S Sathiamoorthy, A (Journal of Spices and Aromatic Crops, 2002)
Experiments conducted at Horticultural College and Research Institute, Periyakulam and Horticultural Research Station, Thadiankudisai (TNAU) to study the effect of different plant growth regulators (NAA, GA3, BA and 2,4-D) indicated that spraying NAA (50 ppm) has improved many commercially desirable parameters like number of berries per spike, volume and weight of berries and yield in black pepper (Piper nigrum L.). Benefit cost ratio, however, was the highest in the treatment 2,4-D (10 ppm). The high cost of chemicals outweighed the yield except in the case of 2,4-D.